Non-Formal Adult Education: Challenges and Prospectsof 21st Century - Ogienko, Olena; Terenko, Olena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article defines the essence and significance of adult non-formal education as an important component of the system of continuing education; analyzes changes in the definition of the phenomenon of non-formal adult education, its role and place in the knowledge society; emphasizes on the importance of development of mechanisms for validation of results of non-formal and informal adult education, training of and ragogues; outlines perspectives of its development.
Keywords: adult education; non-formal adult education; knowledge society; lifelong learning; institutionalization; validation; training